2009
DOI: 10.1097/pai.0b013e318169fc1c
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of HER2 Breast Cancer Testing

Abstract: HER2 status is of great clinical value in breast tumors for the identification of those patients who are eligible for trastuzumab therapy. There is a debate about the advantages and disadvantages of immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) and where, when, how, and who would perform HER2 testing. The purpose of this study was to analyze clinical and analytic validity and clinical utility for HER2 testing (IHC and FISH) for the appropriate selection of breast cancer patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 34 publications
3
58
0
Order By: Relevance
“…These cases had negative HercepTest results (IHC 0 or 1+) but were amplified by FISH. Such HER2 FISH-amplified and IHC-negative cases are well described in the literature 12 and have recently been found to represent 3.5% of IHC 0 and 5.8% of IHC 1+ cases. 20 Considering the frequency of IHC 0 and 1+ cases in this study, between 4 and 5 IHC-negative-and-FISH-positive samples would be expected.…”
Section: Commentmentioning
confidence: 81%
See 2 more Smart Citations
“…These cases had negative HercepTest results (IHC 0 or 1+) but were amplified by FISH. Such HER2 FISH-amplified and IHC-negative cases are well described in the literature 12 and have recently been found to represent 3.5% of IHC 0 and 5.8% of IHC 1+ cases. 20 Considering the frequency of IHC 0 and 1+ cases in this study, between 4 and 5 IHC-negative-and-FISH-positive samples would be expected.…”
Section: Commentmentioning
confidence: 81%
“…Overall, the percentage of agreement (concordance) was calculated, and k statistics were also used to assess agreement between the 2 methods and to describe agreement among the different pathologists. 12 All statistical analyses were done using SPSS 17 or 18 for Windows (SPSS Inc, Chicago, Illinois).…”
Section: Data Handling and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this may indicate that the current recommendation that the HER2 amplification status be assessed by IHC or FISH, with the latter considered as the gold standard, might show exceptions. Indeed, the nonconcordance between protein expression and gene amplification is about 17% for IHC scores of 2ϩ (46).…”
Section: Targeted Mass Spectrometry In Formalin-fixed Tissuesmentioning
confidence: 99%
“…Using cell lines, it was possible to establish a standardized IHC procedure and scoring system in which cells containing Ͻ20,000 receptors would show no staining (0), cells containing approximately 100,000 receptors would show partial membrane staining with Ͻ10% of the cells showing complete membrane staining (1ϩ), cells containing approximately 500,000 receptors would show light to moderate complete membrane staining in Ͼ10% of the cells (2ϩ), and cells containing approximately 2,300,000 receptors would show strong, complete membrane staining in Ͼ10% of the cells (3ϩ). Studies have shown that when a standardized IHC assay is performed on specimens that are carefully fixed, processed, and embedded, there is good to excellent correlation between gene copy status and protein expression levels [162][163][164][165]. However, the ability to accurately determine HER-2 protein expression status by IHC can be significantly impacted by technical issues accentuated by the tissue fixation in formaldehyde, tissue processing, and embedding procedure in heated paraffin wax.…”
Section: Slide-based Assaysmentioning
confidence: 99%